First record of Latris lineata (Forster, 1801) in the Southwest Atlantic Ocean - Waessle, Juan A.; Milessi, Andrés C. (Zootaxa, 2013)
Striped trumpeter, Latris lineata (Forster 1801), is an important deep-water by-catch and recreational fisheries species in New Zealand and Australia (Tracey & Lyle 2005; Beentjes et al. 2010). The species can grow to a relatively large size (1200 mm total length, 25 kg body weight) and live more than 40 years old (Tracey & Lyle 2005; Beentjes et al. 2010). It is regarded as a southern circum-global species widely distributed in the temperate waters of Australia, New Zealand, sub-Antarctic Auckland Island, the Gough and Tristan Da Cunha Island groups, the southern Atlantic Ocean, the Amsterdam and St. Paul Island groups in the southern Indian Ocean, and possibly across the South Pacific to the Juan Fernández Islands and Chile (Nelson 1994; Beentjes et al. 2010; Froese & Pauly 2012) and more recently the Foundation seamount in the southern Pacific Ocean (Roberts 2003). From these accounts their distribution is limited to a latitudinal belt spanning from 35º S to 51º S (Roberts 2003; Tracey et al. 2007). However, the striped trumpeter has never been reported from the southwest Atlantic.